Penggunaan Media Belajar Untuk Meningkatkan Kemampuan Membaca Permulaan - Fahmiyah, Auliya Ul; Kuswandi, Dedi; Wahyuni, Sri (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Early reading literacy is an important foundation in the development of early childhood literacy skills that have a direct impact on their readiness to enter primary education. The urgency of this research is based on the low awareness of the importance of literacy stimulation from an early age and the limited utilization of contextual learning media. This study aims to examine in depth the concept of early reading literacy, the learning approaches used in its introduction, and the effectiveness of learning media in supporting the development of these skills. This research uses the literature study method by systematically tracing and reviewing more than twenty sources of current scientific literature, both in the form of journal articles, books, and research reports. The data analysis technique was conducted qualitatively through thematic analysis approach to identify key themes relevant to the topic. The results of the study show that learning media designed with a concrete and fun approach, such as literacy boards and phased word play, can significantly increase children's learning motivation and phonological understanding. The contribution of this study is not only to enrich the conceptual understanding of early literacy but also to provide practical recommendations in the selection and development of learning media that are suitable for early childhood characteristics. More broadly, the findings provide new directions for curriculum development and literacy learning strategies in the context of Early Childhood Education (ECED).